The Effect of strategy (Team-Pair-Solo) on selective attention and performance of medium and long handling in football (Journal of the College of Basic Education, 2025)
This study aims to prepare educational exercises and use them on vocabulary in the strategy of complex thinking in the practical physical education lesson for basketball, and to learn about the impact of a strategy (Team-Pair-Solo) in selective attention and the performance of the skills Between the results of the tribal and posttests of the two experimental research groups and the control in the selective attention and the performance of the skills of medium and long football, there are statistically significant differences between the results of the dimensional tests of the experimental and control groups in the selective attention and the performance of the skills of medium and long football, and I adopted the experimental approach to the design of the experimental groups. The equivalent officer, and the research community determines the fifth -grade middle school students in the preparatory of Tariq bin Ziyad within the formations of the Resaca Education Directorate/2, for the academic year (2023/2024), The total number of (93) students, who are inherently distributed, are equal to the three people, (A), (B), and (C), the research sample was chosen from them randomly from two divisions, two to reach (62) students at (66.667 %) of this Society, with (31) students for each of them, and after creating the tools of measurement on selective attention and skill performance, educational exercises were prepared and employed in this strategy and applied them over a period of (8) weeks in the physical education lessons by one lesson per week for each skill (4) Lessons and after the end of the experiment and address the results (SPSS), the conclusions and recommendations were that the employment of educational exercises to perform the skills of medium and long football handles with strategic vocabulary (Team-Pair-Solo) in practical lessons suit the fifth preparatory students, and that the application of educational exercises on vocabulary (Team-Pair-Solo) in practical lessons helps improve the level of selective attention, It helps in improving the performance of both the middle and long handling skills of students who study with them, and by superiority of their peers who study without them, and it is necessary to increase the interest of football teachers in measuring the selective attention when teaching their students to perform the midwives of medium and long handling in order to provide support and support for them in improving The skill performance of football, and interest in observance of individual differences must be increased when applying a strategy (Team-Pair-Solo) and working on the multiplicity and diversification of educational positions and tasks in a way that meets the achievement of educational goals to teach the skill performance in football.